2020
DOI: 10.1002/adem.202000519
|View full text |Cite
|
Sign up to set email alerts
|

Customizing the Pore Structure and Properties of Freeze‐Cast Porous Titanium by Zirconium Acetate Additive

Abstract: Porous titanium scaffolds with high porosity and connected macropores are fabricated by adding zirconium acetate to control the ice crystal growth during freeze casting. The influences of zirconium acetate additives on the phase composition, pore structure, and mechanical properties of porous titanium are studied. As modified by zirconium acetate, the X‐ray diffraction peaks of titanium moves to a smaller angle, and the zirconium is evenly distributed on the titanium matrix. With the increase in the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Our previous studies have shown that during the preparation of the titanium scaffold by the freeze casting, as the zirconium concentration increases, the pore structure changes from lamellar to honeycomb. [ 25 ] This article first discussed the effect of freezing temperature on the honeycomb structure with the same addition of zirconium acetate. The morphology of titanium scaffolds prepared at different freezing temperatures was characterized by scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies have shown that during the preparation of the titanium scaffold by the freeze casting, as the zirconium concentration increases, the pore structure changes from lamellar to honeycomb. [ 25 ] This article first discussed the effect of freezing temperature on the honeycomb structure with the same addition of zirconium acetate. The morphology of titanium scaffolds prepared at different freezing temperatures was characterized by scanning electron microscope (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the presence of zirconium acetate in the slurry, the polyhedral structure of ice crystals was changed during the freezing, and the honeycomb pores were obtained after sublimation to remove the ice crystals. [ 25 ] In addition, significant differences in the pore size and wall thickness of the honeycomb pores were observed. Figure shows the average pore size and wall thickness variation of porous titanium with freezing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations